2012
DOI: 10.1002/bmb.20576
|View full text |Cite
|
Sign up to set email alerts
|

Is the undergraduate research experience (URE) always best?: The power of choice in a bifurcated practical stream for a large introductory biochemistry class

Abstract: Science undergraduate courses typically cater to a mixed-learner cohort, with a diversity of motivations and skills. This diversity introduces pressure for designers of the practical laboratory curriculum. Students who are struggling with the course need a series of tasks that begin simply, and transition to more conceptually difficult material. More capable students need opportunities for conceptual extension and creative activity. In this report, we examine an approach we have used to address this problem in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
62
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 34 publications
1
62
0
Order By: Relevance
“…ALURE was initially developed as a means for engaging a group of self-selecting biochemistry students in a real research project (Rowland et al ., 2012). Today, the model has been successfully adapted into a range of science disciplines, undergraduate levels, and institutions (Rowland et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ALURE was initially developed as a means for engaging a group of self-selecting biochemistry students in a real research project (Rowland et al ., 2012). Today, the model has been successfully adapted into a range of science disciplines, undergraduate levels, and institutions (Rowland et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Today, the model has been successfully adapted into a range of science disciplines, undergraduate levels, and institutions (Rowland et al ., 2016). The ALURE model is described in detail in Rowland et al (2012) and Rowland et al (2016), and we briefly restate it here. ALURE allows students to complete research projects during the contact time that is normally dedicated to traditional laboratories or workshops during a unit of study.…”
Section: Introductionmentioning
confidence: 99%
“…Following on to third year coursework, students apply techniques in DNA analysis and protein expression in an In Focus laboratory and reporting assessment tasks as part of second and third year ALURE modules 30,31 . The range of learning gains observed following ALURE participation align with graduate attributes desired by STEM employers 8 -improvement in practical competencies for pathology and research laboratories, and generic transferable skills applicable to workplaces both in and out of science [30][31][32] .…”
Section: Alure: Authentic Large-scale Undergraduate Research Experiencesmentioning
confidence: 69%
“…Given the impact of engaging with undergraduate research on student retention within science programs 21,22 , the long-term value of exposure to research-based learning early in undergraduate education should not be underestimated 34 . focus-group interviews, the ALURE team consistently reported student-learning gains in scientific skills following the completion of ALURE modules 30,31 , with higher gains observed in critical thinking and problem-solving skills when compared to traditional practical modules 32 . Undergraduate research is a high-impact activity that can be of great benefit to students, and the ALURE project has demonstrated that it can be a valuable addition to the instructor's toolkit to bolster student-learning outcomes in transferable skills.…”
Section: Alure: Authentic Large-scale Undergraduate Research Experiencesmentioning
confidence: 97%
“…More frequently these types of open-ended labs are being associated with areas of active research related to faculty scholarship (examples from recent Innovation series include refs. [3,4]). …”
mentioning
confidence: 99%